Wheat ATIs: Characteristics and Role in Human Disease - Geisslitz, Sabrina; Shewry, Peter; Brouns, Fred; America, Antoine H. P.; Caio, Giacomo Pietro Ismaele; Daly, Matthew; D'Amico, Stefano; De Giorgio, Roberto; Gilissen, Luud; Grausgruber, Heinrich; Huang, Xin; Jonkers, Daisy; et al. (Frontiers in Nutrition, 2021)
The α-amylase/trypsin-inhibitors (ATIs) comprise about 2-4% of the total wheat grain proteins and may contribute to natural defense against pests and pathogens. However, they are currently among the most widely studied wheat components because of their proposed role in adverse reactions to wheat consumption in humans. ATIs have long been known to contribute to IgE-mediated allergy (notably Bakers’ asthma), but interest has increased since 2012 when they were shown to be able to trigger the innate immune system, with attention focused on their role in coeliac disease which affects about 1% of the population and, more recently, in non-coeliac wheat sensitivity which may affect up to 10% of the population. This has led to studies of their structure, inhibitory properties, genetics, control of expression, behavior during processing, effects on human health and, most recently, strategies to modify their expression in the plant using gene editing. We therefore present an integrated account of this range of research, identifying inconsistencies and gaps in our knowledge and identifying future research needs.